Rivaroxaban as an Alternative Agent for Heparin‐Induced Thrombocytopenia. (10th June 2020) - Farasatinasab, Maryam; Zarei, Behnaz; Moghtadaei, Mehdi; Nasiripour, Somayyeh; Ansarinejad, Nafiseh; Zarei, Masoumeh
Abstract: Heparin‐induced thrombocytopenia (HIT) is a high‐risk adverse drug reaction because of its associated risk of life‐ and limb‐threatening thrombosis. Rivaroxaban may be considered as an ideal nonheparin anticoagulant alternative for the management of HIT. In this preliminary retrospective study, the efficacy and safety of rivaroxaban to control the clinically suspected HIT (4Ts score 4 points or greater) were evaluated. Patients with chronic kidney disease, hepatic impairment, mechanical heart valves, and active bleeding were excluded. Forty‐two eligible patients who received rivaroxaban for clinically suspected HIT were evaluated by medical records review, with 12‐month follow‐up after the first dose of rivaroxaban. End points included confirmed thrombosis (primary end point), mortality, and adverse treatment‐related events. HIT‐associated thrombosis was found in 17/42 (40.5%) patients before receiving rivaroxaban. After rivaroxaban therapy, platelet counts normalized in all patients, with only 1/42 (2.3%) patients developing new thrombosis. No hemorrhagic event was recorded in the patients. Twelve patients (28.6%) died, but the cause of death was not related to the thrombosis, hemorrhage, or adverse effects of rivaroxaban. Our findings are consistent with the available emerging data, suggesting that rivaroxaban is a safe and effective drug for the management of clinically suspected HIT. Rivaroxaban is a particularly valuable treatment option in developing countries, where there are issues of cost and availability of approved alternative agents.